Робототехника - Андрианов Ю. Д. Юрий Дмитриевич; Бобриков Э. П.; Гончаренко В. Н.; Довбня Н. М.; Жавнер В. Л.; Загороднюк В. Т.; Зайцева Е. В.; Зенкевич С. Л.; Иоффе Ф. С.; Климов В. А.; Попов Е. П. Евгений Павлович; Юревич Е. И. (Автоматические манипуляторы и робототехнические системы)
Доп. тит. с указ. серии